Outcome Of Conservative Management Of Blunt Abdominal Trauma In Children - Asghar, Taram; Malana, Muhammad Ali; Khan, Muhammad Musa; Burki, Sadia; Mirza, Hamza Hussain; Chachudury, Amjad (Biological and Clinical Sciences Research Journal, 2025)
Blunt abdominal trauma (BAT) is a leading cause of pediatric morbidity and mortality, particularly in low-resource settings like Pakistan, where road traffic accidents (RTAs) and falls are major contributors. The standard of care has shifted from mandatory surgical intervention to non-operative management (NOM) for hemodynamically stable patients with solid organ injuries. This study evaluates the outcomes of conservative management of pediatric BAT in a tertiary care hospital in Pakistan, assessing its success rate, complications, and factors contributing to treatment failure. Methods: This prospective observational study was conducted at Pakistan Institute of Medical Sciences (PIMS), Islamabad, over six months (October 2024 to March 2025). A total of 90 pediatric patients (≤16 years) with confirmed BAT were enrolled. Patients were stratified based on injury severity using the American Association for the Surgery of Trauma (AAST) grading system and managed conservatively if hemodynamically stable. Primary outcomes included NOM success rate, need for surgical intervention, and mortality. Secondary outcomes included hospital length of stay, blood transfusion requirements, and complications such as secondary hemorrhage and delayed splenic rupture. Data were analyzed using SPSS version 26, with a p-value of <0.05 considered statistically significant. Results: NOM was successful in 78 patients (86.7%), with failure observed in 12 patients (13.3%), primarily those with severe injuries requiring surgical intervention. The most commonly injured organs were the spleen (40.0%) and liver (38.9%). RTAs were the leading cause of BAT (53.3%), followed by falls (30.0%). Complications included secondary hemorrhage (11.1%), delayed splenic rupture (6.7%), and infection (10.0%). ICU admission was required in 24.4% of cases, while 27.8% required blood transfusions. The mean hospital stay was 5.7 ± 2.3 days, with prolonged stays observed in severe cases. Conclusion: This study demonstrates that NOM is a safe and effective approach for managing pediatric BAT in Pakistan, with a high success rate and favorable patient outcomes. The findings highlight the importance of strict hemodynamic monitoring, timely transfusion support, and selective surgical intervention in high-risk cases. Given the increasing burden of pediatric trauma due to RTAs and falls, efforts should be directed toward improving trauma care infrastructure, enhancing training for NOM protocols, and implementing preventive strategies to reduce pediatric injury rates in Pakistan.